Evaluation of maize and sunflower production in a semi-arid area using in-field rainwater harvesting - Botha, John Jacobus (University of the Free State, 2006)
Subsistence farmers occupy a large area east of Bloemfontein around Thaba Nchu in the Free State Province of South Africa. They do not enjoy food security because the area is marginal for crop production. There are three reasons for this: (a) low and erratic rainfall that amounts to a mean of 543 mm per annum; (b) a corresponding high evaporative demand of 2198 mm per annum; (c) dominantly duplex and clay soils on which rainwater productivity (RWP) is low due to high runoff (R) and evaporation (Es) losses. It was hypothesised that the in-field rainwater harvesting (IRWH) technique could improve crop yields compared to conventional tillage (CON), and thereby serve to improve food security. Field experiments were conducted on the Glen/Bonheim; Glen/Swartland (dark brown A horizon); Khumo/Swartland and Vlakspruit/ Arcadia ecotopes to study the benefits of the IR WH technique on maize and sunflower yields. This thesis distinguishes between ex-field (REx) and in-field runoff (RIn). RIn is transportation of water over the 2 m runoff strip in the IR WH technique. REx occurs on CON and represents a loss of water and soil. Runoff and sedimentation results indicate that IR WH stops REx completely and has the ability to harvest extra rainwater in the basins through RIn and minimize sedimentation. The results also indicate that mulch on the runoff area decreases RIn and sedimentation. The Es process with different surface coverings was studied on two ecotopes viz. Glen/Bonheim and Glen/Swartland (red-brown A horizon). The soil coverings were as follows: bare soil; stone and organic mulch covering 50% of the surface; and organic mulch covering 100% of the surface. The studies were conducted during summer (69 days) and winter (52 days). Results indicated that the % cover affected Es more than mulch type, and that the influence of mulch on Es was more efficient when the drying-out period did not exceed 16 days. New terminology for the various Es stages was introduced. The role of Eo, water content and hydraulic conductivity during the Es process were clarified. Es measurements shallower than 300 mm were shown to be unreliable. Field experiments were conducted on four ecotopes over two to seven growing seasons during the period 1996/1997 to 2002/2003 with maize and sunflower. The treatments were CON; IRWH with a bare basin and bare runoff area (BbBr); IRWH with organic mulch in the basins and a bare runoff area (ObBr); IR WH technique with organic mulch in the basins, stones on the runoff area (ObSr); IRWH technique with organic mulch in the basins, organic mulch on the runoff area (ObOr); IRWH technique with stones in the basins, organic mulch on the runoff area (SbOr). Results showed that IR WH significantly increased maize and sunflower yields compared to CON. This was shown to be due to the ability of IR WH to stop REx completely; enhance RIn and its resulting beneficial redistribution of water in the soil profile; minimize Es/ET, and contribute towards higher transpiration. Both yield and RWP results showed that IRWH stabilises crop production on these ecotopes, compared to CON. Comparing the IR WH techniques revealed that there was a consistent trend in yield and RWP viz. ObSr> ObOr ~ SbOr > ObBr> BbBr. All the IR WH treatments with mulch on the runoff area produced higher RWP values and yield increased between 7 and 16% compared to ObBr. Although Es/ET results indicated that the IR WH treatments with mulch on the runoff area lost smaller portions of ET to Es than ObBr, mulch type on the runoff area and basins did not significantly affect Es in any of the years. The most reliable way to describe the effectiveness with which rainwater was converted into grain by various techniques was by using the parameter RWPn. It was computed by using long-term experimental and simulated yield data, which included rainfall during the fallow and growing seasons. An empirical crop water stress model "Crop Yield Prediction for Semi-Arid Areas" (CYP-SA) was developed. Model composition and validation results with maize and sunflower are described. CYP-SA was used to make long-term maize and sunflower yield predictions with long-term climate data (8I-year period). Cumulative probability functions of simulated long-term maize and sunflower yields have shown that IR WH is significantly superior to CON. The ObSr treatment was shown to be the best. It was also shown that it is advisable to plant maize or sunflower early in January, especially when the soil water profile is between ¾ full and full. The JRWH technique was introduced to rural communities In the target area to improve household food production. The thesis reports on the rapid spread of the application of JRWH amongst homesteads, and on its ability to eradicate poverty at household level. Selected case studies were reported. Very promising results were obtained showing that households can reduce poverty by selling the produce. The five pillars of sustainability, as defined by Smyth & Dumanski (1993) viz. agronomic productivity; crop production risk; conservation of natural resources; economic viability and social acceptability, were investigated in relation to JRWH. Results indicate that in the agro-ecological and socio-economic environment present in the rural communities around Thaba Nchu CON was non-sustainable and that JRWH was sustainable.

Bestaansboere bewoon 'n groot area oos van Bloemfontein in die Vrystaat Provinsie van Suid Afrika. Hulle geniet nie voedsel sekuriteit nie omrede die area marginaal is is vir gewas verbouing. Daar is drie redes hiervoor: (a) lae en wisselvalige reënval met 'n gemiddelde jaarlikse reënval van 543 mm; (b) ooreenstemmende hoë verdampingsaanvraag (Eo) van 2198 mm per jaar; (c) hoofsaaklik dupleks en kleigronde waarop die reënwater produktiwiteit (RWP) laag is agv hoë afloop (R) en verdampings verliese (Es). Die hipotese was dat landeryreënwateropvang (IRWH) tegniek gewas opbrengste kan verbeter in vergelyking met konvensionele bewerking (CON), en sodoende voedsel sekuriteit verbeter. Veld eksperimente is uitgevoer om die voordele van IR WH op mielie en sonneblom obrengste te bestudeer op die Glen/Bonheim; Glen/Swartland (donkerbruin A horison); Khumo/Swartland en Vlakspruitl Arcadia ekotope. Die verhandeling onderskei tussen buite landse (REx) en binne landse afloop (RIn). RIn is die vervoer van water oor die 2 m afloop area in die IR WH tegniek. REx kom op die CON voor en word geasosieer met water en grond verliese. R en sedimentasie resultate dui aan dat IRWH REx geheel en al stop en die potensiaal het om ekstra reënwater in die bakkie area op te vang deur RIn en sedimentasie van bakkies vertraag. Die resultate dui aan dat RIn en sedimentasie van die bakkies beinvloed word deur deklae op die afloop area. Es vanaf kaal grond, klip en organiese deklae wat 50% van oppervlak bedek, en organiese deklaag wat 100% van oppervlak bedek was bestudeer gedurende somer (69 dae) en winter (52 dae) periodes. Die resultate bewys dat % bedekking 'n groter invloed op Es het as deklaag tipe en dat deklae baie meer effektief is as die uitdroog siklus korter is as 16 dae. Nuwe terminologie vir die verdampings proses is bekend gestel en die rol van Eo, water inhoud an hidroliese gelydingsvermoë gedurende Es word word verduidelik. Es meetings vlakker as 300 mm is onakkuraat. Veld experimente op vier ekotope oor periodes wat strek vanaf twee tot sewe jaar (1996/97 - 2002/03) was uitgevoer met mielies en sonneblom. Die behandelings was CON, IRWH met kaal bakkie en afloop areas (EbBr); IRWH met organiese deklaag in bakkie area en kaal afloop area (ObBr); IRWH met organiese deklaag in bakkie area en klip deklaag op afloop area (ObSr); IRWH met organiese deklaag in en op bakkie en afloop areas (Obar); IRWH met klip deklaag in bakkie area en organiese deklaag op afloop area (Sbar). Resultate dui aan dat IR WH mielie en sonneblom opbrengste betekenisvol verhoog teenoor CON. Die redes hiervoor word toegeskryf aan die vermoë van IRWH om REx te stop; RInte bevorder en die daaropvolgende herverspreiding van water in die profiel bevorder; die verlaging van Es/ET wat aanleiding gee tot hoër transpirasie. Opbrengs sowel as RW Presultate dui aan dat die IR WH tegniek gewas produksie stabiliseer op die ekotope in vergelyking met CON. Vergelyking van die IRWHtegnieke ten opsigte van opbrengs en RWP dui 'n konstante tendens aan van ObSr> Obtsr> SbOr > ObBr> BbBr. Al die IRWH behandelings met deklae op die afloop area het hoër RWP waardes sowel as opbrengs verhogings van tussen 7 en 16% geinduseer in vergelyking met ObBr. Alhoewel Es/ET resultate aandui dat dat die IRWH behandelings met deklae op die afloop area kleiner hoeveelhede van ET aan Es verloor het, het deklaag tipe op die afloop sowel as bakkie areas Es nie betekenisvol beinvloed gedurende enige van die jare nie. Die mees betroubare, gewenste en aanvaarbare manier om die effektiwiteit waarmee verskillende tegnieke reënwater omgeskakel in graan opbrengs is deur gebruik te maak van die parameter RWPn, met langtermyn eksperimentele data oor 'n hoeveelheid agtereenvolgende seisoene wat die braak en groeiseisoen insluit. 'n Empiriese gewas water stremmings model "Crop Yield Prediction for Semi-Arid Areas" (CYP-SA) is ontwikkel. Model samestelling en validasie word beskryf vir mielies en sonneblom. CYP-SA met langtermyn klimaat data (81 jaar) is gebruik om langtermyn mielie en sonneblom opbrengs voorspellings te maak. Kummalitiewe waarskynlikheids funksies van langtermyn mielie en sonneblom opbrengste dui aan dat IRWH superieur is bo CON, ObSr is die beste behandeling, en dat mielies en sonneblom vroeg in January geplant moet word verkieslik wanneer die grond water profile tussen % vol en vol is. Die IRWH was bekendgestel in landelike gemeenskappe in die teiken area om huishoudelike voedsel sekuriteit te bevorder. Die verhandeling bespreek die onverwagte verspreiding van die toepassing van die tegniek onder huishoudings en die potensiaalom armoede op 'n huishoudelike vlak te verlig deur gebruik te maak van gevallestudies. Baie belowende resultate is verkry wat aandui dat huishoudings armoede verlig deur hul produkte te verkoop. Die vyf pilare van volhoubaarheid soos aangedui deur Smyth & Dumanski (1993), nl. agronomiese produktiwiteit; gewas produksie risiko; bewaring van natuurlike hupbronne; ekonomiese vohoubaarheid en sosiaal aanvaarbaarheid was bestudeer. Volhoubaarheids resultate van CON en IR WH binne die spesifieke agro-ekologiese and sosio-ekonomiese omgewing teenwoording in die landelike gemeenskappe rondom Thaba Nchu dui aan dat CON nie volhoubaar is nie en IRWH wel.
Thesis (Ph.D. (Soil, Crop and Climate Sciences))--University of the Free State, 2006
Keywords: Corn -- Water requirements -- South Africa -- Thaba Nchu; Sunflowers -- Water requirements -- South Africa -- Thaba Nchu; Rain and rainfall -- South Africa -- Thaba Nchu; Water harvesting -- South Africa -- Thaba Nchu; Semi-arid; Ex-field and in-field runoff; In-field rainwater harvesting; Conventional tillage; Rainwater productivity; Sustainability; Agronomic productivity; Crop production risk; Conservation of natural resources; Economic viability; Social acceptability; Ecotope; Water stress model; Evaporation